(untitled) (International journal of artificial intelligence, 2025)
This article describes an integrated pest management method against the raspberry bud moth (Schreckenstenia festaliella). The pheromone trap is a device equipped with a lure that contains a pheromone dispenser in the form of a rubber capsule treated with a mixture of attractant substances. The study presents the results of using pheromone traps to monitor the raspberry moth population under open field conditions.